Smart security system for home (IOT) - Abd Oun, Muhamed Obed (2020)
This research project is about security home system with IoT. The project will uses Arduino UNO microcontroller as a core component integrated all the sensors, process the sensors' signals and transmit the signals to the WiFi module. At the receiver, there will be one platform or Apps designed to display the signals. Typical signals are the alarm activation ON and OFF signal. Two sensors will be used. One is step switch sensor and second one is ultrasonic sensor. The step switch sensor is used to detect an intruder break in the house through door or window whereas the ultrasonic sensor is used to detect to a mobile intruder around the building campus. These sensors' signals are digital. They are first process inside the microcontroller. By uisng ESP8266 WiFi module, the sensors' signals will be send over an internet network. At the end of the project, a small prototype security system based on IoT will be developed. Keywords: IoT, security, Internet, WiFi, Apps and Arduino microcontroller.